Achieving Sustained Competitive Advantage in Indonesia’s Construction Sector: An Integrated Decarbonization Strategy - Eko Prasetyadi Rachmat; Arif Satria; Siti Amanah (Transpublika Publisher, 2025)
Indonesia’s construction sector significantly contributes to national economic growth but also poses environmental challenges due to high carbon emissions. This study explores how PT Wijaya Karya (Persero) Tbk (WIKA) can develop a sustained competitive advantage through decarbonization strategies. Employing an exploratory qualitative approach, the research integrates the Flourishing Business Model Canvas (FBMC) to assess WIKA’s current business model, the Sustainability Balanced Scorecard (SBSC) to evaluate its sustainability strategy, and the Natural Resource-Based View (NRBV) with Dynamic Capabilities (DC) to recommend future strategies. Data were collected through in-depth interviews with board members and analysis of annual and sustainability reports. Findings reveal WIKA’s commitment to ESG implementation, yet highlight gaps in carbon performance and strategic alignment. The study proposes a roadmap emphasizing emission efficiency, circular innovation, and ESG-driven leadership as pillars of long-term competitiveness in green construction. The insights contribute to practical and academic discourse on sustainable transformation in state-owned enterprises.